2011
DOI: 10.4204/eptcs.48.5
|View full text |Cite
|
Sign up to set email alerts
|

Rule-based transformations for geometric modelling

Abstract: The context of this paper is the use of formal methods for topology-based geometric modelling. Topology-based geometric modelling deals with objects of various dimensions and shapes. Usually, objects are defined by a graph-based topological data structure and by an embedding that associates each topological element (vertex, edge, face, etc.) with relevant data as their geometric shape (position, curve, surface, etc.) or application dedicated data (e.g. molecule concentration level in a biological context). We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…At that point, the possibility to deal with domain-related information (called embeddings) was the main bottleneck of the approach. The introduction of I-labeled graph in [33] solved this issue and defined DPO rewriting for graphs where nodes are labeled by a family of labels. Jerboa [17] offers a graphical rule editor along with a syntax checker that guarantees the consistency of G-map rules (both for the topological aspect and the omission of geometric aspect).…”
Section: Geometric Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…At that point, the possibility to deal with domain-related information (called embeddings) was the main bottleneck of the approach. The introduction of I-labeled graph in [33] solved this issue and defined DPO rewriting for graphs where nodes are labeled by a family of labels. Jerboa [17] offers a graphical rule editor along with a syntax checker that guarantees the consistency of G-map rules (both for the topological aspect and the omission of geometric aspect).…”
Section: Geometric Modelingmentioning
confidence: 99%
“…In topology-based geometric modeling, these data are referred to as embedding. In [33], embeddings were defined as a family of node labels with appropriate consistency constraints and conditions. Since rules can modify both the topology and the embeddings of an object, conditions to preserve the embedding consistency in meta-rules were studied in [34].…”
Section: Graph Transformations Applied To Topology-based Geometric Mo...mentioning
confidence: 99%
“…Similarly, in Figure 10(b), nodes a, b, c, d, e, and f that belong to the same face are labeled with the same yellow color. This property is captured by an embedding constraint [7]: Definition 6 (Embedded graph and embedded generalized map). Let π : ⟨o⟩ → τ be an embedding operation with ⟨o⟩ an orbit type and τ a data type.…”
Section: Embedding Representationmentioning
confidence: 99%
“…To extend their usability, we showed that they offer a safer design of topological operations to produce a topological-based geometric modeler [8], which was more accessible than traditional ad hoc implementations that are fastidious to code and vulnerable to consistency bugs. In [7], we defined a new graph category that allows nodes to have multiple labels in order to represent the multiple embedding types simultaneously (e.g., a face being labeled by both its color and its porosity). We proved the existence of graph transformations in this category and introduced a new type of dedicated variables and operators to express embedding transformations in rules.…”
mentioning
confidence: 99%
See 1 more Smart Citation